2005
DOI: 10.1007/s00383-005-1541-3
|View full text |Cite
|
Sign up to set email alerts
|

Taurine and cholestasis associated to TPN. Experimental study in rabbit model

Abstract: Taurine seems to be essential in the newborn for bile acid (BA) tauroconjugation, and its deficiency has been implicated in total parenteral nutrition-associated cholestasis (TPN-AC). Our purpose was to study the relationship between taurine (Ta) and TPN-AC in rabbits, which have a similar biliary metabolism to that of humans. We used 40 young rabbits, fed for 10 days according to the following four groups: GA [10] given TPN, with amino acid solution (AA) but without taurine (Ta) or its AA-precursors (methioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…evidenced by loss of bile canaliculi microvilli and elevated serum bile acids. These findings mirror those reported in PNALD [12][13][14]. Bile acid transporter proteins, such as multidrug resistance protein, are located in the canaliculi microvilli and play an important role in bile acid metabolism.…”
Section: Groupsupporting
confidence: 86%
“…evidenced by loss of bile canaliculi microvilli and elevated serum bile acids. These findings mirror those reported in PNALD [12][13][14]. Bile acid transporter proteins, such as multidrug resistance protein, are located in the canaliculi microvilli and play an important role in bile acid metabolism.…”
Section: Groupsupporting
confidence: 86%
“…In the subsequent rabbit experiments by Loff [20], he confirmed that the histologic damage to the liver was obviously caused by the TPN solution itself, regardless of whether additional enteral feeding was also supplied. In another study of the relationship between taurine and TPN-associated cholestasis (TPN-AC) in rabbits, Moran and his colleagues [21] found that diffused liver steatosis, dilated canaliculi, abundant bile plugs, and loss of microvilli appeared after 10 days of TPN in rabbits. There were signs that taurine may protect against TPN-AC.…”
Section: Discussionmentioning
confidence: 96%
“…PN is associated with changes in plasma BA composition; the excess amounts of some BA cause hepatotoxic effects related to PN, and the administration of taurine can decrease the toxicity of BA. Conjugation of BA to taurine and glycine is mediated by the same competitive enzyme, 20 and in preterm infants, where the taurine is a provisionally essential amino acid, due to either an inability of endogenous synthesis or a nutrition deficit, conjugation of BA with glycine would be expected to increase. In fact, in the current study, GCA concentrations were significantly elevated in the T0 group (Table 2) as compared with healthy controls, which we attribute to the number of preterm infants in the T0 group (7/9).…”
Section: Resultsmentioning
confidence: 99%